ANALYSIS OF MORAL VALUES IN THE UPIN IPIN CARTOON FILM EPISODE 14 (TUDUNG SAJI MENGKUANG) - Ni Kadek Karmaeni (INJOSEDU: International Journal of Social and Education, 2025)
Cartoon films are the most popular films for children, not only children, cartoon films are also often watched by teenagers and adults. because cartoon films have a concise storyline and pictures. Not many words are used. Easy to understand and recognize. The message is usually fresher and clearer. So cartoon films are one type of animated film that is the most popular choice or show for children. One of the children's cartoon films that airs on TV is Upin & Ipin. in the Upin & Ipin film using Malay / Malaysian. But the language used is easy to understand by Indonesian children because Malaysian and Indonesian have little similarity. This study aims to analyze the cartoon film "Upin & Ipin as a cartoon film that contains values and morals. This study is a descriptive study. The data source used is the Upin & Ipin cartoon film on TV / YouTube. The data analysis technique uses qualitative descriptive. The results of the analysis show that: The Upin & Ipin film can be used as a medium to instill values and morals and character education in children which include: loyalty, cooperation, mutual motivation, gentleness, mutual respect between friends, perseverance, not easily discouraged, enthusiasm and respect for parents.